2018
DOI: 10.12998/wjcc.v6.i14.807
|View full text |Cite
|
Sign up to set email alerts
|

Ileal bronchogenic cyst: A case report and review of literature

Abstract: We herein report a rare case of ileal bronchogenic cyst that was found in a 39-year-old Chinese man. He had no symptoms and the physical examination was normal. Tumor markers were within the normal range. Abdominopelvic enhanced computed tomography showed a mass in the lower abdominal cavity and the tumor had a complete capsule. Diagnostic laparoscopy was then performed, which showed that a spheroid mass with a complete capsule was located at the antimesenteric border of the distal ileum 20 cm from the ileocec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As bronchogenic cysts are a rare congenital disease, the pathogenesis of this disease is not yet known. Lots of medical doctors and researchers consider bronchogenic cysts to be congenital broncho saccharin changes caused by the abnormal development of trachea, bronchial trees or lung buds during the embryonic period[ 6 , 10 ]. Shah et al [ 7 ] reported a total of 86 cases of bronchogenic cysts, and about 74% of these patients were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As bronchogenic cysts are a rare congenital disease, the pathogenesis of this disease is not yet known. Lots of medical doctors and researchers consider bronchogenic cysts to be congenital broncho saccharin changes caused by the abnormal development of trachea, bronchial trees or lung buds during the embryonic period[ 6 , 10 ]. Shah et al [ 7 ] reported a total of 86 cases of bronchogenic cysts, and about 74% of these patients were male.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of skin bronchogenic cysts was reported by Seybold and Clagett[ 1 ] in 1945. Bronchogenic cysts may occur in various areas, such as the mediastinum[ 2 ], lungs[ 3 ], heart[ 4 ], stomach[ 5 ], peritoneum[ 6 ] and in other areas. The disease is more commonly diagnosed in childhood than in adulthood[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, if tissue necrosis or hemorrhage occurs, the pathological results might be affected. Differential diagnosis of the abdominal bronchogenic cysts includes gastrointestinal stromal tumor, Meckel’s diverticulum, intestinal duplication cyst, and lymphangioma[ 8 ]. We consider that preoperative imaging is an important approach for differentiation of abdominal bronchogenic cysts from gastrointestinal stromal tumor, Meckel’s diverticulum, intestinal duplication cyst and lymphangioma .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of bronchogenic cysts was not revealed clearly. However, a reasonable speculation is that bronchogenic cyst is related to embryonic abnormal development that the tumor arises from primitive foregut because of the lung bud development malformation (5).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of bronchogenic cysts was not revealed clearly. However, a reasonable speculation is that bronchogenic cyst is related to embryonic abnormal development that the tumor arises from primitive foregut because of the lung bud development malformation ( 5 ). Therefore, (the) many bronchogenic cysts located in the lungs and heart have been reported, but little has been reported in the abdominal cavity, especially in retroperitoneum ( 5 ).…”
Section: Discussionmentioning
confidence: 99%